Critérios da iluminação elétrica urbana - Roizenblatt, Isac (2009)
The city at night differs from the city during the day, because nocturnal urban lighting must satisfy several functions such as to create a new environment, to increase the awareness of the beauty and diversity of landscapes, to ensure safety and to attend to the psychomotor needs, to guide through space marks, to highlight places according to their specificity, to enrich festivals and spectacles, and to facilitate leisure. Nevertheless,historically speaking, it has been observed that lighting has been developed to attend to the demands of the cars and has forgotten the demands of the citizens. People s needs at night should be the main objective of the urban lighting, whether it is for the resident, for the student, for the worker or for the tourist. What it is pursued is the lighting which includes a search for identity for historic structures, commercial areas, educational and hospital buildings, as well as for leisure centers. This paper shows that there is a lack of suitable lighting for the cities today. It analyses the several functions of the urban lighting, in order to check its compliance, and need for improvement.